Tradisi Perkawinan Muka-Ptukar Masyarakat Dataran Waeapo: - Hukunala, Marselina (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2024)
In the community of Buru Island, the muka ptukar tradition is a practice of exchanging women as a substitute for dowry. In this tradition, the groom's sister is exchanged with the bride’s brother. The purpose of this tradition is to ease the groom’s family in paying dowry and as a recognition of self-identity. This study aims to describe and analyse the muka ptukar tradition of the Waeapo plains community in Buru Island, from the perspective of gender and exchange theories. This study uses a qualitative method, with descriptive and analytical research types. This paper uses several data collection techniques, such as literature, interviews, and observations. The location of this research is the Waeapo plains, Waepsalit Village, Metar Hamlet and Lele Village, Buru Island. The results of the study indicate that the muka ptukar tradition is still alive today, especially in Waepsalit Village, Metar Hamlet, and Lele Village. In fact, in this practice, women are often considered as “exchange tools” for the benefit of men that women are forced to become “dowry”. This practice is a form of discrimination against women, illustrating the strength of patriarchal culture, but at the same time showing certain cultural values, such as good name and family dignity.